Analisis Al-Urf dalam Hukum Islam terhadap Pelaksanaan Perkawinan Adat Nokolontigi dan Mandiupasili Dalam Perkawinan Suku Adat Kaili Kelurahan Kabonena Kecematan Ulujadi Sulawesi Tengah - Andiahmad Ramadhani; M. Abdurahman; Encep Abdul Rojak (Bandung Conference Series: Islamic Family Law, 2025)
Abstract. Indonesia is an archipelago country because it consists of thousands of islands and has various tribes and different customs. Differences in place of residence also distinguish variations in the livelihoods of customs and habits of the community. Customs or traditions are often defined as regulations that apply in a particular society, and include various norms that govern life together. The concept of "Ada" in "Ada ri Tana Kaili" refers to customs or rules that are firmly held by the community. These rules are not only social norms, but also have binding power and must be respected by members of society. "Ada" reflects the cultural heritage and values that have been passed down from generation to generation, and is the basis for social interaction and life together in the Kaili Tribe community. This study uses qualitative research because this research is based on basic human observations. The existence of this empirical legal approach is carried out in order to find out how the procedures for implementing the Kaili tribe's traditional traditions regarding the "Nokolontigi and Mandiupasili" traditional marriage and Al-Urf's analysis of the Kalili tribe's traditional marriage traditions "Nokolontigi and MandiuPasili" in Kabonenan Village, Ulujadi District, Central Sulawesi. Applying good and in-depth communication between the author and the phenomenon being discussed to provide good information about the procedures for carrying out the "Nokolontigi and Mandiupasili" traditional marriage traditions of the Kaili tribe, as well as Al-Urf's analysis of the "Nokolontigi and Mandiu Pasili" traditional tradition in Kabonena Village. In the Kaili tribe, Nokolontigi and Mandiupasili have values, namely historical, cultural and social values. In the implementation of the Nokolontigi and Mandipasili customs, there is a lot of mixing between Islamic law and customary law. Several offerings in the form of natural plant materials symbolize the relationship between humans and the surrounding environment. The traditional traditions of Nokolontigi and Mandiupasili in weddings of the Kaili tribe in Kabonena Village, Central Sulawesi, are in line with Islamic law and contain positive values. This tradition functions to strengthen family ties, ask Allah SWT for safety, and reflects tolerance towards existing culture. The implementation of these two traditions includes al-'urf shahih, which does not change what is haram into halal. Abstrak. adat istiadat yang berbeda-beda. Perbedaan tempat tingal juga membedakan variasi dalam mata pencaharian adat istiadat dan kebiasaan masyarakat. Adat atau tradisi sering didefinisikan sebagai peraturan yang berlaku dalam suatu masyarakat tertentu, dan mencakup berbagai norma yang mengatur kehidupan bersama. Konsep "Ada" dalam "Ada ri Tana Kaili" merujuk pada adat atau aturan yang dipegang teguh oleh masyarakat. Aturan-aturan ini bukan hanya sekadar norma sosial, tetapi juga memiliki kekuatan yang mengikat dan harus dihormati oleh anggota masyarakat. "Ada" mencerminkan warisan budaya dan nilai-nilai yang telah diwariskan dari generasi ke generasi, dan menjadi landasan bagi interaksi sosial dan kehidupan bersama dalam masyarakat Suku KailiPenelitian ini penulis mengunakan penelitian kualitatif karena peneliti ini di dasarkan pada pengamatan dasar manusia. Adanya pendekatan yuridis empiris ini dilakukan agar mengetahui bagaimana tata cara pelaksanaan tradisi adat suku kaili tentang perkawinan adat “Nokolontigi dan Mandiupasili” serta analisis Al-Urf terhadap tradisi adat perkawinan suku kalili “Nokolontigi dan MandiuPasili” di Kelurahan Kabonenan Kecamatan Ulujadi Sulawesi Tengah. Menerapkan kemunikasi yang baik dan mendalam antara penulis dengan fenomena yang dibahas untuk memberikan informasi yang baik tentang tatacara melangsungkan perkawinan tradisi “Nokolontigi dan Mandiupasili” tradisi adat suku kaili, serta analisis Al-Urf tentang tradisi adat “Nokolontigi dan Mandiu Pasili” Kelurahan KabonenaPada masyarakat suku adat kaili Nokolontigi dan Mandiupasili mempunyai nilai-nilai yaitu nilai sejarah, budaya dan sosial. Dalam pelaksanaan adat Nokolontigi dan Mandipasili, terdapat banyak percampuran antara syariat Islam dan hukum adat. Beberapa sesajen yang berupa bahan-bahan tumbuhan alam melambangkan hubungan manusia dengan lingkungan sekitarnya.Tradisi adat Nokolontigi dan Mandiupasili dalam perkawinan suku Kaili di Kelurahan Kabonena, Sulawesi Tengah, sejalan dengan hukum Islam dan mengandung nilai-nilai positif. Tradisi ini berfungsi memperkuat ikatan kekeluargaan, memohon keselamatan kepada Allah Swt, serta mencerminkan toleransi terhadap budaya yang telah ada. Pelaksanaan kedua tradisi ini termasuk al-‘urf shahih, yang tidak mengubah yang haram menjadi halal.